Spatial Ecology and Movement of Ornate Box Turtles in the Escalating Drought Conditions of the Great Plains Ecoregion - Rachel E. Weaver; Thanchira Suriyamongkol; Sierra N. Shoemaker; Joshua T. Gonzalez; Ivana Mali (Fire)
Shifts in global climate patterns can alter animal behavior, including movement and space use. The southwestern United States of America is currently undergoing a period of megadrought, which can have profound consequences on small ectothermic organisms like box turtles. We radiotracked eight adult ornate box turtles (Terrapene ornata) in eastern New Mexico from September 2019 to July 2022, when the environmental conditions transitioned from a dry season with low cumulative precipitation in 2020 to high cumulative precipitation in 2021, followed by a regression to exceptional drought conditions that culminated with a high-intensity wildfire in early 2022. Turtles exhibited greater mean daily movement and were more active in 2021 in comparison to 2020 and 2022. Turtles were least active in 2022, while mean daily movement was comparative to 2020. All turtles in our study exhibited homing behavior after the wildfire, but individual responses varied. While some turtles initially moved out of the burned area and returned within a month, others remained inactive within a small portion of the burned area. The greatest movement was documented in one female turtle following the wildfire, whose home range expanded to seven times the average maximum annual home range size observed among other turtles. Overall, this is the first documentation of T. ornata response to highly altered habitat after high-severity wildfire.